Employee ownership and union labor: the case of United Steel Workers of America. (27th May 2017) - Hoffman, Richard C.; Brown, Marvin O.
Abstract: Union–management relations in the U.S. are best described as adversarial. However, under certain circumstances, they can become cooperative. One example of the latter was the role of trade unions in the conversion of firms to employee ownership. Firm ownership (entrepreneurship, capitalism) by employees has increased in recent years. Specifically, we focus on the use of 'investment bargaining' (i.e. buyouts using ESOPs) by the United Steelworkers of America during the decades of the 1980s and 1990s as the steel industry faced serious declines. This study applies some basic union–management bargaining frameworks for examining both primary (e.g. case studies) and secondary data to demonstrate that the USW's adoption of investment bargaining is consistent with their pragmatic approach in preserving the employment of their members. The impact and the implications of the union's efforts in this area as well as the future role of unions in employee buyouts are also discussed.